The Function of the Media on Family Planning on Community Perception and Participation in Sorong Papua - Wijayanti, Lumastari Ajeng; Mainassy, Meillisa Carlen; Nurhaedah, Nurhaedah; Juwariah, Siti; Aji, Sulistyani Prabu; Nurseskasatmata, Satria Eureka (International Journal of Health Sciences, 2023)
Attention to the Family Planning (KB) program received priority during the New Order era. The family planning program had even become a government program at the beginning of that period. Before becoming a government program, Family Planning had begun to be socialized by several individuals or private institutions who had an interest in the program. The aim of this research is to find out information sources that provide family planning information to the public, differences in perceptions according to information sources, differences in participation according to perception, differences in participation according to sources of information, and to find out 5 differences in participation according to perception which are controlled by level of education, number of children they have and desire to have another child. The method used in this research is census. Data analysis was carried out using the chi-square statistical test using the SPSS program version 17.0. The research results showed that the majority of respondents obtained family planning information through television (58.2%), and there was an influence of information on perceptions and participation in family planning. This is proven by the differences in perception according to exposure to information, participation according to perception and participation according to exposure to information convincingly with a confidence level of 95%. In the control variables, there are significant differences in participation according to education level and number of children (95%), while there is no significant difference in participation according to the desire to have more children. Information determines participation in family planning practices, but does not determine the desire to have more children. This is due to different perceptions of the value of children, so the desire to have more children does not influence participation in family planning practices.